Do Rumen Bacteroidetes Utilize an Alternative Mechanism for Cellulose Degradation? - Naas, A. E. (American Society of Microbiology, 2014)
Uncultured and therefore uncharacterized Bacteroidetes lineages are ubiquitous in many natural ecosystems which specialize in lignocellulose degradation. However, their metabolic contribution remains mysterious, as well-studied cultured Bacteroidetes have been shown to degrade only soluble polysaccharides within the human distal gut and herbivore rumen. We have interrogated a reconstructed genome from an uncultured Bacteroidetes phylotype that dominates a switchgrass-associated community within the cow rumen. Importantly, this characterization effort has revealed the first preliminary evidence for polysaccharide utilization locus (PUL)-catalyzed conversion of cellulose. Based on these findings, we propose a further expansion of the PUL paradigm and the saccharolytic capacity of rumen Bacteroidetes species to include cellulose, the most abundant terrestrial polysaccharide on Earth. Moreover, the perspective of a cellulolytic PUL lays the foundation for PULs to be considered an alternative mechanism for cellulose degradation, next to cellulosomes and free-enzyme systems.